High, but variable prevalence of Sarcocystis cruzi infections in farm-raised American bison (Bison bison) beef destined for human consumption - Larissa S. de Araujo; Aditya Gupta; Marianne Dias Papadopoulos; Doaa Naguib; Jacquin Battle; Oliver Kwok; Asis Khan; Benjamin Rosenthal; Jitender P. Dubey (Parasites & Vectors)
Abstract Background Bison (Bison bison) and cattle (Bos taurus) are closely related (can interbreed) and they also share many parasites. Cattle are commonly infected with one or more of the eight named Sarcocystis species: Sarcocystis hirsuta, S. cruzi, S. hominis, S. bovifelis, S. heydorni, S. bovini, S. sigmoideus and S. rommeli. Among these, the full life-cycle is known only for S. cruzi. Sarcocystis cruzi (transmitted via canids) is recognized as the most pathogenic Sarcocystis species, causing abortion, low milk yield and poor body growth. It has been experimentally cross-transmitted from cattle to bison and vice versa. Methods We tested 200 bison tongues from three commercial sources (farms) (Nebraska #141; South Dakota #36; New Jersey and Pennsylvania #23). Frozen tongues were purchased and examined for Sarcocystis infection using light microscopy, histology and quantitative PCR (qPCR) targeting 18S ribosomal DNA (18S rRNA) of S. cruzi. Lesions associated with degenerating sarcocysts were studied. The intensity of Sarcocystis infection in histological sections was quantitated. Results Sarcocystis cruzi-like infections were detected in 129 of 141 (91.5%) tongues from Nebraska, 36 of 36 (100%) tongues from South Dakota and two of 23 (8.6%) tongues from New Jersey and Pennsylvania. Sarcocysts were detected in histological sections stained with hematoxylin and eosin in 167 of 200 samples. Light microscopy examination revealed that the sarcocysts had thin walls (< 1 µm thick) and appeared to be S. cruzi. However, in two samples, sarcocysts had thicker walls measuring up to 2.3 µm wide and 154 µm long and the sarcocyst wall was not striated; these two samples could not be characterized further. In three tongues, degenerating sarcocysts were recognized; two of these were associated with thick-walled sarcocysts. Molecularly, S. cruzi from bison was identical to that in cattle. Conclusions In the present study of bison tongues, S. cruzi was the only species identified in bison using both molecular and morphological methods. An unidentified species of Sarcocystis found in two bison samples needs further study. Graphical abstract